2011
DOI: 10.1093/gbe/evr077
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Small Repeat Sequences on Bacterial Genome Evolution

Abstract: Intergenic regions of prokaryotic genomes carry multiple copies of terminal inverted repeat (TIR) sequences, the nonautonomous miniature inverted-repeat transposable element (MITE). In addition, there are the repetitive extragenic palindromic (REP) sequences that fold into a small stem loop rich in G–C bonding. And the clustered regularly interspaced short palindromic repeats (CRISPRs) display similar small stem loops but are an integral part of a complex genetic element. Other classes of repeats such as the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 104 publications
2
66
0
1
Order By: Relevance
“…MITEs are small, AT-rich DNA sequences (0.1 to 0.5 kb) containing terminal inverted repeats, often displaying a TA dinucleotide motif at their extremities and being surrounded by target-site duplications (Fig. 1B) (4,34,35). They often possess the recognition sequences necessary for their mobility but do not encode a transposase.…”
Section: Mobile Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…MITEs are small, AT-rich DNA sequences (0.1 to 0.5 kb) containing terminal inverted repeats, often displaying a TA dinucleotide motif at their extremities and being surrounded by target-site duplications (Fig. 1B) (4,34,35). They often possess the recognition sequences necessary for their mobility but do not encode a transposase.…”
Section: Mobile Elementsmentioning
confidence: 99%
“…These new junctions have the potential to alter the function or expression of proteins. Finally, rearrangements can influence the structure of the chromosome, with indirect effects on phenotype (4). For example, a large inversion in the chromosome of Escherichia coli can have dramatic effects on cell viability (5,6).…”
mentioning
confidence: 99%
“…It has been shown in numerous systems that repeating elements (repeats and/or IS; Dataset S8) can be mediators of genomic plasticity (61,62,78); however, the direct impacts of these repeats are not always so clear. For example, high IS density in the genome of Lactobacillus acidophilus has been described (79), and despite the propensity of these elements to inactivate genes and facilitate recombination of genomic structure (61), the genome of this isolate still displays high levels of synteny with other sequenced Lactobacilli.…”
Section: Significancementioning
confidence: 99%
“…For example, high IS density in the genome of Lactobacillus acidophilus has been described (79), and despite the propensity of these elements to inactivate genes and facilitate recombination of genomic structure (61), the genome of this isolate still displays high levels of synteny with other sequenced Lactobacilli. Because it has also been shown that partial IS sequences can inhibit transposition (78,80), it is possible that these repeats/pseudogenes have not been deleted because they are controlling transposition in the transposase-heavy IMS101. Others have hypothesized that the conserved repeat structures observed in some bacteria could function as recombinationdependent "promoter banks" for adaptation to new conditions, thereby allowing relatively quick "rewiring" of metabolism in subpopulations (59,62,81).…”
Section: Significancementioning
confidence: 99%
“…Variability in DNA repeats could help provide information about functional and evolutionary information on genetic diversity of such organisms (van Belkum, 1999a). Van Belkum as well as Delihas (van Belkum et al, 1999;Delihas, 2011), discovered and revealed the vital role sequence repeats play with the regulation of microbial gene expression. The significance of sequence repeats in epidemiologic typing cannot be underestimated (van Belkum, 1999b).…”
Section: Multifaceted Applications Of Repeat Analysismentioning
confidence: 99%